Modelling And Vibration Analysis Of Alveolar Resonance Mechanism Of Ultrasound-Induced Lung Haemorrhage - Devadason, John Jabaraj (2013)
The most widely studied biological adverse effect of the diagnostic ultrasound is the ultrasound-induced lung haemorrhage. The ultrasound-induced lung haemorrhage has been observed in various experimental studies on animals. Nevertheless, the actual mechanism by which the ultrasound-induced lung haemorrhage occurs still remains undetermined and unproven. One of the proposed but unexplored mechanisms is the alveolar resonance mechanism. The hypothetical alveolar resonance mechanism is proposed as the forced vibration and resonance of the alveolar structure by the external ultrasound waves. This modelling and vibration analysis study, theoretically investigates the alveolar resonance mechanism and its capability for producing the ultrasound-induced lung haemorrhage. Firstly, the facet of the alveolar wall was modelled as square and circular membranes with fixedboundary. Then, the application of the linear theory of vibration together with the laws of linear elasticity, unto the membrane models, produced the equations of fundamental frequency and threshold pressure. The fundamental frequency of each membrane model represents the natural frequency of the alveolar structure at which the alveolar resonance mechanism may occur.